PENGARUH CURRENT RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSET PADA PT LIPPO KARAWACI TBK PERIODE 2013-2023 - Febriyanti; Bulan Oktrima (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the Current Ratio and Debt To Asset Ratio on Return On Assets at PT Lippo Karawaci Tbk. The research method used is descriptive quantitative and uses statistical analysis. This research uses secondary data, with the population used being the annual financial report at PT Lippo Karawaci Tbk for 2013-2023. The sample for this data uses reports of financial position and profit and loss from 2013 to 2023. The results of this research were obtained from descriptive tests, classical assumptions, simple and multiple linear regression, as well as coefficient of determination, correlation and hypothesis tests. Partially the Current Ratio has a significant effect on Return On Assets with a tcount value of 5.073 > ttable 2.306 with a significant value of 0.001 < 0.05, while for partial Debt To Asset results there is a significant influence on Return On Assets with a tcount value of 2.632 < ttable 2.306 with a significant value of 0.030 <0.05. The results of simultaneous testing of the Current Ratio and Debt To Asset Ratio have a significant influence on Return On Assets with significant results of 0.003 < 0.05 and the Fcount value is greater than Ftable (12.871 > 4.46). The results of the coefficient of determination test show that the Adjusted R Square (Adj R2) value is 0.704 or 70.4%, while the remaining 29.6% can be explained by other variables that are not in this research model.